Effects of flooding on seedling establishment in two Australian riparian trees with contrasting distributions; Acacia stenophylla A. Cunn. ex Benth. and Casuarina cunninghamiana Miq. Issue 6 (25th November 2015) - Maxwell, Adam; Capon, Samantha J.; James, Cassandra S.
Abstract: Riparian habitats in arid and semi‐arid landscapes are characterised by unpredictable flooding and drought with favourable opportunities for seedling establishment limited to short periods following floodwater recession. Tree species persisting under such conditions might therefore be expected to exhibit traits that facilitate seedling growth and survival in the face of unpredictable flooding and drought. We examined seedling growth in response to flooding in two common eastern Australian riparian tree species with contrasting distributions: Acacia stenophylla, common in lowland riparian habitats of the arid and semi‐arid interior where average annual rainfall is below 500 mm, and Casuarina cunninghamiana, widespread in upland and coastal catchments with average annual rainfall over 500 mm. We conducted a glasshouse experiment to investigate seedling growth and survival over 90 days under a range of watering treatments including continuous flooding, flooding followed by drying and continuously moist conditions. Seedlings of both species exhibited high levels of flood tolerance, apparently facilitated by a capacity to halt growth and delay development rather than via plastic growth responses. Both species also displayed rapid and opportunistic growth in response to moist conditions; however, this was around three‐fold greater in A. stenophylla seedlings. Our results suggest that seedling establishment traits influence the distribution of these widespread riparian species and contribute to the capacity of A. stenophylla to persist under the stressful and unpredictable conditions characteristic of arid and semi‐arid riparian habitats. Copyright © 2015 John Wiley & Sons, Ltd.